BURNOUT IN ACADEMIC PHYSICIAN DURING COVID-19 PANDEMIC - Dian Puspita Sari; Yoga Pamungkas Susani; Emmy Amalia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2021)
Background: The COVID-19 pandemic has caused tremendous and abrupt changes in all aspects of social life, including healthcare and education. It has caused stress and psychological impact on physicians and other healthcare workers globally. Exposure to chronic occupational stress can lead to burnout. The multiple responsibilities of academic physicians potentially lead to a higher risk of burnout, particularly during this pandemic. This study aimed to obtain burnout profiles in academic physicians and factors associated with burnout during the COVID-19 pandemic.Methods: This was a cross-sectional study. The MBI-HSS was used to measure the three dimensions of burnout. Academic physicians' perception of distance learning, involvement in the clinical care of COVID-19 patients, involvement in faculty management, and healthcare facilities management were also included in the survey. Results: Among 42 participants (response rate 56%), 45.2% provided care to COVID-19 patients, 42.9% were involved in the management of healthcare facilities, and 35.7% in faculty management. Median of Emotional Exhaustion (EE) was 12 (1-35), Depersonalization (DP) 6 (0-19) and Personal Accomplishment (PA) 32.5 (16-47). Based on Z-score for each dimension, 23.8% have high EE, 16.7% high DP, 50% low PA, and 11.9% categorized as burnout. Involvement in healthcare facilities management and providing care for COVID-19 patients were significantly associated with higher EE (p = .030 and p = .029 respectively), while the perception of the workload of distance learning associated significantly with higher EE (p = .046) and DP (p = .014). Conclusion: Workload related to clinical work, healthcare management, and distance learning, associated with higher burnout in academic physicians during COVID-19 pandemic.